Pembentukan Karakter Kewirausahaan Siswa SMK melalui Implementasi Manajemen Edupreneurship - Mugiarto, Mugiarto (Jurnal Kridatama Sains dan Teknologi, 2023)
Edupreneurship is an activity that emphasizes creative or innovative efforts by schools to obtain school achievements and increase income. The implementation can be through teaching factories or business centers. In Vocational High Schools combining the implementation of learning in schools with the implementation of industrial work practices in partner work institutions, synchronously and systematically, which aims to lead students to mastery of certain work skills, so that they become graduates with relevant abilities as expected. This study aims to describe and analyze in depth the management and edupreneurship programs in the formation of the entrepreneurial character of students in SMK. The method used in this research is library research using a philosophical approach. The data collection technique used is the documentation technique, namely collecting data material in the form of sources from books, articles and others related to the object of study. The results showed that edupreneurship management was carried out based on the Vocational School Edupreneurship Development Guidelines from the Ministry of National Education, through five stages, namely the preparation of organizational structures, product quality assurance, service quality assurance, marketing and marketing strategies for edupreneurship programs. Second, the edupreneurship program in forming the entrepreneurial character of students in vocational schools, through teaching factories and business centers. The teaching factory program is carried out with the 6M model. This program can foster self-confidence, task and result-oriented, risk-taking, and leadership. The business center program through business practices by observing market activities, taking an inventory of consumer needs, placing orders, selling goods by setting their own prices, can foster a significant entrepreneurial spirit, self-confidence, task and result oriented, Dare to take risks, honest and diligent. Keywords: Management, Edupreneurship, Teaching Factory, Business Center, Entrepreneurship, Vocational High School